2013
DOI: 10.15835/nsb518341
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Seedling Development of Seeds from Different Parkia biglobosa (Jacq) G. Don Trees

Abstract: The effect of daylight, continuous illumination and acid scarification on the seed germination and seedling vegetative growth (epicotyl and hypocotyl lengths, and number of secondary roots) of different Parkia biglobosa were investigated in the Plant Physiology Laboratory University of Ilorin, Ilorin Kwara State Nigeria. Seeds from two out of the twenty six Parkia tree samples (trees B and T) germinated within 24 hours of planting in the daylight germination study while seeds from another tree (Q) did not germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…2). In an experiment that was carried out to assess the impact of sulphuric acid on the seedling growth of Parkia biglobosawere, it was found that the length of the radicle and plume was the highest when the Parkia biglobosawere seeds were soaked sulphuric acid (Adeyemi et al, 2013). In an experiment to evaluate the impact of various pre-sowing treatments on seed germination of Bladder-Senna, Beikmohammadi et al (2012) observed that the highest shoot length was attained when the seeds were treated with concentrated (98%) H2SO4 for 15 minutes.…”
Section: Germination Valuementioning
confidence: 99%
“…2). In an experiment that was carried out to assess the impact of sulphuric acid on the seedling growth of Parkia biglobosawere, it was found that the length of the radicle and plume was the highest when the Parkia biglobosawere seeds were soaked sulphuric acid (Adeyemi et al, 2013). In an experiment to evaluate the impact of various pre-sowing treatments on seed germination of Bladder-Senna, Beikmohammadi et al (2012) observed that the highest shoot length was attained when the seeds were treated with concentrated (98%) H2SO4 for 15 minutes.…”
Section: Germination Valuementioning
confidence: 99%